Abrupt changes in the southwest monsoon during Mid-Late Holocene in the western Bay of Bengal. (15th April 2022) - Govil, Pawan; Mazumder, Abhijit; Agrawal, Shailesh; Azharuddin, Syed; Mishra, Ravi; Khan, Hidayatullah; Kumar, Brijesh; Verma, Divya
Graphical abstract: Highlights: Variation in southwest monsoon governs the surface circulation of Bay of Bengal. Reduction in fresh water flux between ∼5.9 and ∼3.7 kyr. A progressive increase in fresh water flux after ∼3.7 kyr. Abrupt increase in fresh water flux related to RWP and MWP extreme events. Abstract: The present work aims to understand the variation in the southwest monsoon (SWM) and the surface water hydrography around the western Bay of Bengal (WBoB). In this study, we used various micropaleontological [planktonic foraminifera relative abundance, planktonic and benthic foraminiferal abundance (PFA and BFA), planktonic/benthic (P/B) ratio], sedimentological [sand %] and oxygen isotope of Globigerinoides ruber (δ 18 O G.ruber ) proxies in a marine sediment core (SK336/3) since last ∼6 kyr before present (BP). The δ 18 O G.ruber, PFA, BFA, and the planktonic foraminifera relative abundance records suggest the reduced freshwater input corresponding to an aridification phase during ∼5.9–3.7 kyr BP, possibly related to the weakening of the SWM in the WBoB. The WBoB has reworded comparatively wetter conditions since ∼3.7 kyr BP suggests increased freshwater input centering around ∼1.8 and ∼0.9 kyr BP, associated with the SWM intensification during the Roman and Medieval Warm Periods (RWP and MWP), respectively. The relative abundance of planktonic foraminifera correlates well with a sand percentage between ∼5.9 and ∼3.7 kyr BP, suggesting a productivity decline due to terrigenous dilution. Significant periodicities of ∼418, ∼165, ∼139, ∼109, ∼97, and ∼86 years are found in the spectral analysis of planktonic foraminiferal relative abundance and δ 18 O G.ruber time-series, corresponding to hydrographic changes in the WBoB due to the influence of solar-driven cyclicity in the SWM during the last ∼6 kyr BP. Comparison of our multi-proxy signatures with other paleo-proxy records during the mid-late Holocene reveals large-scale climate variability in the Northern Hemisphere, related to the changes in solar activity.